Celiac crisis in children in Serbia - Radlovic, Nedeljko (Ital J Pediatr, 2016)
BACKGROUND: To assess the prevalence and risk factors of celiac crisis (CC) in children with classical celiac disease (CD). METHODS: This retrospective study comprised 367 children with classical CD diagnosed from 1994 to 2015. The diagnosis of CD was based on the revised ESPGHAN criteria and CC on acute worsening and rapid progression of chronic diarrhea and vomiting followed by severe dehydration, multiple metabolic derangements and a marked decrease of body weight. RESULTS: Celiac crisis was confirmed in six (1.63 %) children, five in the first and one in the second year of life. In three patients CC was precipitated by rotavirus and in one by Salmonella enteritidis infection, while in the remaining two, except for a too long-standing disease and severe malnutrition, no additional causes of CC were found. CONCLUSION: Celiac crisis in Serbia is still-present in children exclusively below the second year of life as a spontaneous or intestinal infection precipitated complication of previously unrecognized CD.